Wind loading on a low-slope gabled roof: Comparison of field measurements, wind tunnel data, and code provisions. (15th September 2022) - Chavez, M.; Baskaran, A.; Aldoum, M.; Stathopoulos, T.; Geleta, T.N.; Bitsuamlak, G.T.
Highlights: Current wind load provisions for low-slope roofs were established in the 70 s. Verification of the original pressure coefficients is required. An ideal full-scale representation of low-slope roof is monitored and tested in wind tunnel. Wind load provision for Edge zone in NBCC-2020 is currently underestimated. Merging Corner and Edge into a unique "Perimeter" load provision is suggested. Abstract: The current wind load provisions for low-slope roofs in the NBCC were established in the 70 s with wind tunnel experiments using analog data technology. These coefficients have remained almost unchanged. As the wind pressure measurement tools have significantly improved during the past 50 years, verification of the original pressure coefficients is required. The National Research Council of Canada (NRC), in collaboration with the Special Interest Group on Dynamic Evaluation of Roofing Systems (SIGDERS) consortium, conducted a wind load investigation to verify the suitability of the current wind load provisions. The investigation was carried out using both field measurements and wind tunnel simulations. An ideal full-scale representation of the low-slope roof specified in building code was instrumented and continuous data was collected for four years. A duplication of the building was evaluated by two wind tunnels to investigate the effect of critical wind directions. The paper presents the efforts made to make field measurements comparable to wind tunnel data and code provisions. It was observed that records with mean wind a speed above 22 mph (10 m/s) reduce the data variability and maximize reliability, which are important features for the code verification process. The goal of this research is to combine multiple sources of data to verify the suitability of wind load provisions on low-slope roofs. The research focuses on NBCC-2020 as an application. Evidence is presented that the NBCC-2020 provisions for the Roof Edge Zone is currently underestimated and needs to be increased. The study suggests taking the opportunity of Edge provision enhancement to merge Corner and Edge into a unique "Perimeter" load provision. The suggested code change addresses the current underestimation of the Edge Zone coefficients (wind load upgrade), and provides construction simplification to minimize roofing failure associated with labour-induced errors during cladding system installation (constructability upgrade).